EFFECTS OF FREE DAY SECONDARY SCHOOL FUNDS ON STUDENTS’ COMPLETION RATES IN PUBLIC DAY SECONDARY SCHOOLS IN MWALA SUB-COUNTY, MACHAKOS COUNTY, KENYA - SALOME NDUNGWA KISYANGA (Machakos University Press, 2025)
Education plays a crucial role in the progress of any nation. Since independence in 1963, Kenya has witnessed significant growth in its secondary school education sector. Numerous new schools have been built to accommodate the rising number of students seeking secondary education. This has effectively reduced the distance students have to travel to reach their schools, making day schooling more feasible. However, despite the government’s efforts to make education more accessible through initiatives like Free Day Secondary Education (FDSE), there is a concerning trend of high drop-out rates among students before completing the entire four-years of secondary school learning. The government’s objective of ensuring education affordability for all school going children has not fully addressed the persistent issue of students dropping out of school prematurely. This research aimed at examining the effects of FDSE funds on the completion rates of students in public day secondary schools in Mwala Sub-County, Machakos County, Kenya. The four objectives of the study were: to establish the influence of disbursement process of FDSE funding on students’ completion rates in public day secondary schools in Mwala Sub-County, Machakos County, Kenya; to determine the effect of FDSE funding adequacy on students’ completion rates in public day secondary schools in Mwala Sub-County, Machakos County, Kenya; to establish the influence of FDSE funds utilization on students’ completion rates in public day secondary schools in Mwala Sub-County, Machakos County, Kenya; and to examine the effect of extra levies on students’ completion rates in public day secondary schools in Mwala Sub-County, Machakos County, Kenya. The study was grounded in the Systems Theory of Management and used a descriptive survey research design. The study focused on the 52 public day secondary schools located in the specified sub county. The research involved a study population of 52 principals, 208 class teachers, 52 chairpersons, and 52 vice-chairpersons of students’ leaders’ councils in day secondary schools. To ensure representation, the Stratified Sampling Technique was used to divide the schools into seven educational zones. A random sample of 28 principals, 107 class teachers, 28 chairpersons, and 28 vice-chairpersons was selected from each zone using simple random sampling. Data was collected through questionnaires, and the instrument’s reliability was assessed using the test-retest technique with the guidance of supervisors. The reliability index was determined using Pearson’s Product Moment Correlation Coefficient method, with an r>0.7 indicating high internal reliability. Experts assessed the appropriateness of the research items and evaluated there suitability to determine validity. While descriptive statistics like frequencies, percentages, and means were used to examine the quantitative data, the qualitative data was analyzed thematically using story forms. The Statistical Packages for the Social Scientists computer programme Version 24 was used for statistical data analysis, and the results were discussed in narrative form and percentages and presented graphically as frequency tables, and figures. The study established that FDSE funding is inadequate for the required learning/teaching resources. The delay in disbursement of the funds affects the quality of learning due to inadequate resources. This compels schools to charge extra levies. As a result, students are sent home for extra levies and those who cannot afford drop out of school. The Ministry of Education should develop clear policy and guidelines to ensure adequacy of funds, disbursement of funds on time and prudent utilization of funds and to curb charging of extra levies in schools. The study found out that the students completion rates were below 70% of the learners who enroll in public day secondary schools in Mwala Sub-County. The high enrolment rates are not in tandem with the completion rates.